Decreasing Malpractice Claims by Reducing Preventable Perinatal Harm. (22nd August 2016) - Riley, William; Meredith, Les W.; Price, Rebecca; Miller, Kristi K.; Begun, James W.; McCullough, Mac; Davis, Stanley
Abstract : Objective: To evaluate the association of improved patient safety practices with medical malpractice claims and costs in the perinatal units of acute care hospitals. Data Sources: Malpractice and harm data from participating hospitals; litigation records and medical malpractice claims data from American Excess Insurance Exchange, RRG, whose data are managed by Premier Insurance Management Services, Inc. (owned by Premier Inc., a health care improvement company). Study Design: A quasi‐experimental prospective design to compare baseline and postintervention data. Statistical significance tests for differences were performed using chi‐square, Wilcoxon signed‐rank test, and t ‐test. Data Collection: Claims data were collected and evaluated by experienced senior claims managers through on‐site claim audits to evaluate claim frequency, severity, and financial information. Data were provided to the analyzing institution through confidentiality contracts. Principal Findings: There is a significant reduction in the number of perinatal malpractice claims paid, losses paid, and indemnity payments (43.9 percent, 77.6 percent, and 84.6 percent, respectively) following interventions to improve perinatal patient safety and reduce perinatal harm. This compares with no significant reductions in the nonperinatal claims in the same hospitals during the same time period. Conclusions: The number of perinatal malpractice claims and dollar amount of claims payments decreased significantly in the participating hospitals, while there was no significant decrease in nonperinatal malpractice claims activity in the same hospitals.